Social isolation-induced increase in NMDA receptors in the hippocampus exacerbates emotional dysregulation in mice - Chang, Chih-Hua; Hsiao, Ya-Hsin; Chen, Yu-Wen; Yu, Yang-Jung; Gean, Po-Wu (Hippocampus, 2015)
ABSTRACT Epidemiological studies have shown that early life adverse events have long‐term effects on the susceptibility to subsequent stress exposure in adolescence, but the precise mechanism is unclear. In the present study, mice on postnatal day 21–28 were randomly assigned to either a group or isolated cages for 8 weeks. The socially isolated (SI) mice exhibited a higher level of spontaneous locomotor activity, a longer duration of immobility in the forced swimming test (FST), significantly less prepulse inhibition (PPI) and an increase in aggressive (but not attack) behavior. However, acute stress markedly exacerbated the attack counts of the SI mice but did not affect the group housing (GH) mice. SI mice exhibited higher synaptosomal NR2A and NR2B levels in the hippocampus as compared to the GH mice. Whole‐cell patch clamp recordings of CA1 neurons in hippocampal slices showed that the SI mice exhibited a higher input‐output relationship of NMDAR‐EPSCs as compared to the GH mice. Application of the NR2B‐specific antagonist ifenprodil produced a greater attenuating effect on NMDAR‐EPSCs in slices from the SI mice. NMDAR EPSCs recorded from the SI mice had a slower deactivation kinetic. MK‐801, CPP and ifenprodil, the NMDA antagonists, reversed acute stress‐induced exaggeration of aggressive and depressive behaviors. Furthermore, acute stress‐induced exacerbation of attack behavior in the SI mice was abolished after the knockdown of NR2B expression. These results suggest that social isolation‐induced increased expression of NMDA receptors in the hippocampus involves stress exacerbation of aggressive behaviors. Amelioration of aggressive behaviors by NMDA antagonists may open a new avenue for the treatment of psychopathologies that involve outbursts of emotional aggression in neglected children. © 2014 Wiley Periodicals, Inc.